'The infyrmitie of fayth': Anti-Nicodemism and religious insecurity in Marian and early Elizabethan England - Griffiths, Andrew (2022)
Anti-Nicodemites condemned all religious conformity during the Reformation. They did so in general terms but did not openly condemn named individuals. Anti-Nicodemism was a reflection of religious insecurity and did not indicate the real existence of a hidden group that identified as Nicodemites and had a clear religious identity. The thesis argues that the study of anti-Nicodemism in Marian and early Elizabethan England helps historians understand less about the lived experience of Nicodemism than it does the anxieties of the anti-Nicodemites themselves. In essence, Nicodemism was a loose and generalised negative stereotype with very little reference to real people, and not a lived identity or a true representation of the experiences. It can only ever be understood from the available historical evidence as an externally imposed identification, rather than a coherent and articulated theological position developed and held by adherents. The thesis explores whether the acts of dissimulation and conformity led to individual stigma. It uses many private letters and evidence of relationships between conformists, exiles and martyrs. The sources are split between those which would have been public and general, and those which are private – especially letters. Protestants in Mary’s reign had their works published in Emden, Geneva, Strasbourg, and other centres of the European Reformation, whilst works by Catholics in the early years of Elizabeth’s reign were published in Louvain and Antwerp, which were the centres of English Catholic exile. William Cecil was a prominent leader in the Elizabethan Settlement, and the source materials reflect this – this thesis includes detailed analysis of Cecil, and his religious conformity and relationships with anti-Nicodemites. This thesis adds to the scholarship by concluding that whilst there may have been many individual justifications of conforming to another confessional practice, there was no cohesive theory, theology or Nicodemite community in the way imagined by anti-Nicodemites. Anti-Nicodemism was indicative, and an expression, of more generalised religious insecurity; the corpus of anti-Nicodemite writing is not a useful source for understanding religious conformity in Reformation England.